Physical Processes in Lakes - Bengtsson, Lars (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Physical processes are keys for the status of a lake. In this Special Issue, the emphasis is on dissolved oxygen and on exchange of gases, energy and momentum between atmosphere and further mixing and consumption within the water. The studies presented relate to ice-free as well as ice-covered lakes. Field measurements are combined with theoretical approaches.